Grease composition and electronic component using the same

By using liquid resin, polymethacrylic organic particles and inorganic fillers in the grease composition, the gelled composition is formed at high temperature, and the pumping resistance and thermal conductivity of the existing grease composition at high temperature and high humidity is solved, and higher long-term reliability and stability are achieved.

CN116390975BActive Publication Date: 2025-04-22KYOCERA CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080105507.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-09-30
Publication Date
2025-04-22
Estimated Expiration
2040-09-30

AI Technical Summary

Technical Problem

The conventional non-siliconic heat conductivity grease composition lacks pumping resistance under 150°C×1000 cycle conditions, and the thermal conductivity and viscosity stability are not fully studied, making it easy to absorb moisture in a high humidity environment and reduce heat dissipation.

Method used

A grease composition containing liquid resin, polymethacrylic organic particles and inorganic fillers is used to form a gelled composition at high temperature by selecting liquid resin and matching the solubility parameters of polymethacrylic organic particles, thereby reducing pumping and void generation.

Benefits of technology

The pumping production is significantly reduced at 150°C, maintaining thermal conductivity and reducing void generation, ensuring the reliability and stability of electronic components during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116390975B_ABST
    Figure CN116390975B_ABST
Patent Text Reader

Abstract

A grease composition, characterized in that it contains (A) a liquid resin, (B) polymethacrylic acid-based organic particles and (C) an inorganic filler, wherein the (A) liquid resin contains at least one selected from polyols, polyethers and diamine resins, and the (B) polymethacrylic acid-based organic particles are soluble in an organic solvent having a solubility parameter (SP value) of 7.8 to 10.1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a grease composition and an electronic component using the grease composition. Background Art

[0002] In recent years, as electronic components have become more powerful and compact, malfunctions have occurred due to heat generated by the components. Therefore, in order to release the heat generated in each electronic component so that the component can operate stably, a method of using a heat sink has been applied.

[0003] The grease composition can improve heat dissipation by being sandwiched between a heating element and a heat dissipating element. As a grease composition, generally, from the viewpoints of thermal decomposition stability, flame retardancy, etc., a thermally conductive silicone putty composition based on silicone oil and containing zinc oxide or aluminum oxide is known (for example, Patent Document 1).

[0004] However, it is known that since electronic components repeatedly generate heat and cool, there is a large difference in thermal expansion between the heating element and the heat sink, which can cause the grease to become less viscous at high temperatures and be squeezed out (pumping phenomenon). In particular, with the recent increase in power, pumping resistance in the 150°C region is required. For the silicone grease described in Patent Document 1, pumping resistance in the 150°C region has not been fully studied. In addition, it is assumed that silicone grease will produce siloxane gas when used at high temperatures. Since siloxane gas will adhere to electrode contacts and the like to generate silicon dioxide, there is a possibility of causing contact failure.

[0005] Therefore, non-silicone thermally conductive grease compositions that improve the pumping resistance of silicone grease have been proposed (for example, Patent Document 2). These compositions solve the pumping phenomenon by adding a nonionic surfactant to heat-resistant oil to reduce the viscosity drop at high temperatures.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2017-2179;

[0009] Patent document 2: Japanese Patent Application Publication No. 2019-89924. Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, although the pump-out resistance up to 150°C × 100 cycles was studied for the non-silicone thermally conductive grease composition described in Patent Document 2, the pump-out resistance up to 150°C × 1000 cycles, which is required recently, was not studied. In addition, the change in thermal conductivity of the thermally conductive grease composition during long-term use was not confirmed in the above-mentioned grease composition.

[0012] In addition, the non-silicone thermally conductive grease composition may contain volatile components. Among them, since the non-ionic surfactant used to prevent pumping described in Patent Document 2 has a high affinity with water, it is easy to absorb moisture in the environment. Therefore, when the above-mentioned non-silicone thermally conductive grease composition is used for semiconductor power modules for inverters that are often used outdoors, it is likely to easily absorb moisture in a high humidity environment. In addition, in the hygroscopic state, when the temperature of the semiconductor element rises, the absorbed moisture evaporates rapidly to form gaps, and the heat dissipation may be reduced.

[0013] As described above, in the conventional non-silicone thermally conductive grease compositions, studies on maintaining the pump-out resistance and thermal conductivity for a long period of time are insufficient.

[0014] Therefore, the present invention provides a grease composition that reduces the occurrence of pumping out, maintains thermal conductivity and reduces the generation of voids under high temperature conditions, especially around 150°C, and an electronic component in which the grease composition is arranged between a heating element and a heat sink.

[0015] Technical solutions to problems

[0016] The grease composition of the present invention contains (A) a liquid resin, (B) polymethacrylic acid-based organic particles, and (C) an inorganic filler, wherein the (A) liquid resin contains at least one selected from polyols, polyethers, and diamine resins, and the (B) polymethacrylic acid-based organic particles are soluble in an organic solvent having a solubility parameter (SP value) of 7.8 to 10.1.

[0017] The electronic component of the present invention comprises a heat generating element, a heat dissipating element, and the above-mentioned grease composition of the present invention disposed between the heat generating element and the heat dissipating element.

[0018] Effects of the Invention

[0019] The grease composition of the present invention can reduce the generation of pumping out, maintain thermal conductivity and reduce the generation of voids at high temperatures, especially at about 150°C.

[0020] The electronic component of the present invention can fully exert thermal conductivity even when the heating element is at a high temperature of about 150° C. by placing the grease composition of the present invention between the heating element and the heat sink. In addition, the electronic component of the present invention can maintain the same thermal conductivity during subsequent use, and thus has excellent long-term reliability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram showing a schematic configuration of one embodiment of the electronic component of the present invention. DETAILED DESCRIPTION

[0022] Hereinafter, the present invention will be described in detail with reference to an embodiment.

[0023] <Grease composition>

[0024] The grease composition of this embodiment includes: (A) a liquid resin containing at least one selected from a polyol, a polyether and a diamine resin; (B) polymethacrylic acid organic particles dissolved in a solvent having a solubility parameter (SP value) of 7.8 to 10.1; and (C) an inorganic filler.

[0025] In this specification, grease refers to a semi-solid or solid grease obtained by dispersing a thickener in a raw material base oil in accordance with JIS K2220: 2013. It should be noted that the "solid" includes a gel state in which the entire system loses fluidity.

[0026] The grease composition of the present embodiment (hereinafter, also referred to as "the present grease composition") is a composition having grease properties. The present grease composition loses fluidity by heating as described later and changes from a semi-solid state to a gel state due to the action of (B) polymethacrylic acid-based organic particles. Hereinafter, in the present grease composition, the gelled grease composition is also referred to as "the present gel-like composition".

[0027] In this specification, the liquid state of a liquid resin refers to a liquid state at room temperature. Specifically, a liquid component refers to a component having a viscosity of 200,000 mPa·s or less measured at 25°C using an E-type viscometer (e.g., VISCOMETER TPE-100, manufactured by TOKISANGYO). Hereinafter, unless otherwise specified, the viscosity of a liquid substance refers to the viscosity measured at 25°C using an E-type viscometer (e.g., VISCOMETER TPE-100, manufactured by TOKISANGYO).

[0028] In this specification, normal temperature refers to 5 to 40°C, preferably 15 to 30°C.

[0029] The grease composition is used for electronic components, for example, between a heating element and a heat sink in a heat generating component. In this case, the grease composition is applied to at least one of the heating element or the heat sink at room temperature. Thereafter, the heating element and the heat sink are arranged with the grease composition sandwiched therebetween. Alternatively, the grease composition is arranged by injecting the grease composition between the heating element and the heat sink arranged at a predetermined distance.

[0030] Since the grease composition has grease properties and a viscosity described below, it can be applied or injected between the heat generating element and the heat dissipating element in the heat generating component with good operability, and does not require heat treatment such as drying, and the electronic component can be easily assembled.

[0031] When the heat generating component to which the present grease composition is applied reaches a high temperature during use, for example, about 150°C, the present grease composition gels in the process of temperature rise to become the present gel-like composition. Here, in the present grease composition, gelation is achieved by swelling the (B) polymethacrylic acid organic particles among the components contained in the present grease composition with the (A) liquid resin. The temperature at which the present grease composition starts to gel depends on the types of the (A) liquid resin and the (B) polymethacrylic acid organic particles, but is generally 60 to 130°C. In this way, when the heat generating component is at a high temperature, for example, about 150°C, the present grease composition changes with temperature to become the present gel-like composition with less fluidity. As a result, there is almost no pumping out between the heat generating element and the heat dissipating element. In addition, by infiltrating the (A) liquid resin into the (B) polymethacrylic acid organic particles, the (B) polymethacrylic acid organic particles are swollen, thereby making the volatile components in the (A) liquid resin less volatile. As a result, the present gel-like composition can also reduce the generation of voids.

[0032] Furthermore, since the present gel-like composition obtained by gelling the present grease composition has flexibility, even when the shape of the heating element and the heat sink changes due to temperature drop, the composition has excellent shape-changing properties, excellent adhesion even at low temperatures, and can maintain thermal conductivity. In addition, the present gel-like composition can also reduce the generation of volatile components.

[0033] When the present grease composition is used for a heat-generating component, after gelation under the above-mentioned high temperature state, even if the high temperature is restored to normal temperature, the present grease composition still exists between the heat-generating body and the heat-dissipating body in the state of the gelled present gel-like composition. Thereafter, even if the heat-generating body is repeatedly heated up and cooled down, the present gel-like composition formed by the gelation of the present grease composition can maintain the above-mentioned effect, and the property change due to temperature change is small. As a result, the heat-generating component can be used stably for a long time.

[0034] Hereinafter, each component contained in the present grease composition will be described.

[0035] 〔(A) Liquid resin〕

[0036] The (A) liquid resin contained in the present grease composition is a resin that is liquid at room temperature, and is a resin containing at least one selected from polyols, polyethers and diamine resins. The definition of liquid is as above. The (A) liquid resin is a component that makes the present grease composition in a grease-like state by mixing with the solid components contained in the present grease composition, specifically, by mixing with (B) polymethacrylic organic particles and (C) inorganic fillers. In addition, the (A) liquid resin has the function of penetrating into the (B) polymethacrylic organic particles by heating and swelling the (B) polymethacrylic organic particles, thereby gelling the present grease composition into the present gel-like composition. As a result, the present grease composition can reduce the increase in fluidity due to temperature changes during use.

[0037] The heat resistance of the (A) liquid resin is mainly affected by the resin skeleton. In particular, the presence or absence of an aromatic ring in the resin affects the weight reduction at high temperatures. By having such heat resistance, the (A) liquid resin can provide a grease composition with excellent long-term reliability. In addition, the (A) liquid resin can be a resin with low hygroscopicity. When the (A) liquid resin has low hygroscopicity, the generation of voids can be reduced.

[0038] The (A) liquid resin is selected from the above-mentioned specific types of resins, but may be a heat-resistant resin that reduces weight less.

[0039] When the liquid resin (A) contains two or more resins, the mixture obtained by mixing the two or more resins may be in a liquid state. The liquid resin (A) can be obtained by mixing a solid resin with a liquid resin.

[0040] The viscosity of the (A) liquid resin measured at 25° C. using an E-type viscometer, for example, VISCOMETER TPE-100 manufactured by TOKISANGYO, may be 10 to 10,000 mPa·s, or 100 to 1,000 mPa·s.

[0041] (A) The mass reduction rate of the liquid resin at 150°C based on 25°C may be less than 1%. There is no particular lower limit to the mass reduction rate. By making the mass reduction rate less than 1%, for example, when the grease composition is used in a heat-generating component, when the grease composition is arranged between a heat-generating body and a heat-dissipating body, the volatile components can be reduced, and the reduction in heat dissipation characteristics due to the generation of voids can be reduced.

[0042] The mass reduction rate can be calculated as the mass change rate (reduction rate) of the (A) liquid resin before and after heating by leaving it in an oven at 150° C. for 24 hours.

[0043] From the viewpoint of efficiently swelling the polymethacrylic acid organic particles (B), the liquid resin (A) may have high compatibility with the polymethacrylic acid organic particles (B). Specifically, the SP value of the liquid resin (A) may be close to the SP value of the polymethacrylic acid organic particles (B). The SP value of the liquid resin (A) may be 7.3 to 11.5.

[0044] The above-mentioned SP value is a value defined by the normal solution theory introduced by Hildebrand. For example, the smaller the difference in solubility parameters (SP values) of two components is, the greater the solubility is.

[0045] The SP value of the (A) liquid resin can be measured by the same method as the method for measuring the SP value of the (B) polymethacrylic organic particles described later.

[0046] It should be noted that, when the liquid resin (A) includes two or more resins, the SP value of the mixed resin obtained by mixing the two or more resins may be close to the SP value of the polymethacrylic organic particles (B). When two or more liquid resins (A) are mixed and used, the SP value of each of the mixed resins may be close to the SP value of the polymethacrylic organic particles (B).

[0047] Hereinafter, the resin used as (A) the liquid resin will be further described.

[0048] Examples of the polyol include polylactone polyols, polycarbonate polyols, aromatic polyols, alicyclic polyols, aliphatic polyols, polycaprolactone polyols, castor oil polyols, ethylene-vinyl acetate copolymers, polyether polyols, polyester polyols, etc. These may be used alone or in combination of two or more.

[0049] As the polyol, a polyester polyol may be used from the viewpoint of lowering viscosity and heat resistance.

[0050] Examples of the polyester polyol include polyols of a polyol-polycarboxylic acid condensation system and polyols of a cyclic ester ring-opening polymer system.

[0051] Specific commercial products of the polyester polyol include, for example, UNISTER (registered trademark) HR-32 and UNISTER (registered trademark) H-809RB manufactured by NOF Corporation.

[0052] As polyether, there are aromatic hydrocarbon series and phenyl ether series. Polyether can be used alone or mixed with polyol or diamine resin. The ratio when mixed can be polyether: polyol or diamine resin = 50 to 95: 50 to 5 in terms of mass ratio, and can be 70 to 95: 30 to 5 from the viewpoint of heat resistance.

[0053] Examples of the aromatic hydrocarbons include polyethylene terephthalate, polybutylene terephthalate, polybutylene naphthalate, polystyrene, polysulfone, polyethersulfone, polyphenylene sulfide, polyphenylene sulfone, polyarylate, polyetherimide, polyimide, polyamideimide, etc. These may be used alone or in combination of two or more.

[0054] The phenyl ether system includes phenyl ether resins and alkyl phenyl ether resins. Specifically, diphenyl ether, tetraphenyl ether, pentaphenyl ether, alkyl diphenyl ether, monoalkyl triphenyl ether, monoalkyl tetraphenyl ether, dialkyl tetraphenyl ether, polyethylene glycol, polypropylene glycol, polybutylene glycol, poly (1-methylbutylene glycol) perfluoropolyether, polyether monool, polyether diol, polyether triol, etc. can be cited. These can be used alone or in combination of two or more.

[0055] From the viewpoint of heat resistance, the polyether may be a phenyl ether-containing polyether.

[0056] Specific commercial products of the phenyl ether polyether include LB-100, S-3105, S-3103, S-3101, and S-3230 manufactured by MORESCO CORPORATION.

[0057] Examples of the diamine resin include p-phenylenediamine (PDA), m-phenylenediamine, 4,4'-oxydiphenylamine (ODA), 3,3'-bistrifluoromethyl-4,4'-diaminobiphenyl (TFMB), 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,2-bis(anilino)ethane, diamino Diphenyl sulfone, diaminobenzanilide, diaminobenzoic acid ester, diaminodiphenyl sulfide, 2,2-bis(p-aminophenyl)propane, 2,2-bis(p-aminophenyl)hexafluoropropane, 1,5-diaminonaphthalene, diaminotoluene, diaminotrifluorobenzoate, 1,4-bis(p-aminophenoxy)benzene, 4,4'-bis(p-aminophenoxy)biphenyl, diaminoanthraquinone, 4,4'-bis(3-aminophenoxyphenyl)diphenyl sulfone, polytetrahydrofuran-diparaaminobenzoate, etc. These may be used alone or in combination of two or more.

[0058] From the viewpoint of heat resistance, the diamine resin may be polytetrahydrofuran-diparaaminobenzoate.

[0059] As a specific commercial product example of the diamine resin, ELASMER 1000P manufactured by Kumiai Chemical Industries, Ltd. is mentioned, for example.

[0060] From the viewpoint of heat resistance, the liquid resin (A) may contain a polyether. When the liquid resin (A) contains a polyether, the content of the polyether in the liquid resin (A) may be 50 to 95% by mass, or 70 to 95% by mass.

[0061] (A) The liquid resin may contain other resins in addition to the polyol, polyether and diamine resin as necessary. Examples of other resins include epoxy resins and oxetane resins.

[0062] When the (A) liquid resin contains other resins, the content thereof may be 10% by mass or less, 5% by mass or less, or 3% by mass or less.

[0063] The content of the (A) liquid resin in the present grease composition may be 5 to 30% by mass, or 5 to 10% by mass, relative to the total amount of the present grease composition. When the content of the (A) liquid resin is 5% by mass or more, the viscosity of the present grease composition does not become too high, and it becomes easy to become a semi-solid state. On the other hand, when the content of the (A) liquid resin is 30% by mass or less, the viscosity of the present grease composition does not become too low, and the workability becomes good.

[0064] [(B) Polymethacrylic acid organic particles]

[0065] The (B) polymethacrylic acid organic particles used in the present grease composition are components that have the function of adjusting the viscosity of the present grease composition by mixing with the (A) liquid resin together with the (C) inorganic filler at room temperature. In addition, when the (B) polymethacrylic acid organic particles are heated to a predetermined temperature or higher, the liquid component mainly composed of the (A) liquid resin contained in the present grease composition penetrates into the (B) polymethacrylic acid organic particles and swells them, thereby having the function of gelling the present grease composition. Specifically, the (B) polymethacrylic acid organic particles are particles of an organic compound having the above-mentioned function. For the present grease composition, the above-mentioned predetermined temperature depends on the types of the (A) liquid resin and the (B) polymethacrylic acid organic particles, but is generally 60 to 130°C.

[0066] As described above, the organic compound constituting the (B) polymethacrylic acid organic particles may have good compatibility with the (A) liquid resin. Specifically, the SP value of the (B) polymethacrylic acid organic particles may be close to the SP value of the (A) liquid resin. When the SP value of the (B) polymethacrylic acid organic particles is close to the SP value of the (A) liquid resin, the swelling property of the (B) polymethacrylic acid organic particles increases, and the gelation of the present grease composition proceeds well.

[0067] (B) The polymethacrylic acid organic particles are selected from polymethacrylic acid organic particles that are soluble in a solvent having an SP value of 7.8 to 10.1. It should be noted that the "soluble in a solvent having an SP value of 7.8 to 10.1" of the (A) liquid resin or (B) polymethacrylic acid organic particles in this specification means that they are soluble in any one of the solvents having an SP value of 7.8 to 10.1, and can be soluble in a plurality of solvents having different SP values. The SP value of a solvent can be determined by the Fedors method. Whether or not it is soluble in a solvent having an SP value of 7.8 to 10.1 can be determined specifically by the method described in the examples.

[0068] As a solvent for judging whether (B) polymethacrylic acid organic particles are soluble, for example, a solvent having an SP value of 7.0 to 12.7 can be used, and there is no particular limitation as long as the solvent has such characteristics. Examples of such solvents include n-pentane (SP value: 7.0), n-hexane (SP value: 7.3), ethylhexyl acrylate (SP value: 7.8), cyclohexane (SP value: 8.9), ethylbenzene (SP value: 9.0), methyl ethyl ketone (SP value: 9.1), acetone (SP value: 9.9), acetic acid (10.1), isopropyl alcohol (IPA) (SP value: 11.5), and ethanol (SP value: 12.7).

[0069] In terms of solubility in solvents, the (B) polymethacrylic acid-based organic particles are soluble in all solvents having an SP value of 7.8 to 10.1.

[0070] The organic compound constituting the (B) polymethacrylic acid-based organic particles may be an acrylic resin or a polymethacrylate. It should be noted that the acrylic resin is a resin obtained by polymerizing acrylic acid, methacrylic acid and their derivatives as main monomers, and may also contain polymerization units of other vinyl-containing monomers. The polymethacrylate is a resin obtained by polymerizing methacrylate as the main component monomer, and may also contain polymerization units of monomers other than methacrylate, and may also be a partially cross-linked product. From the viewpoint of swelling properties, it may also be a non-cross-linked product.

[0071] Specific examples of polymethacrylates include resins containing methacrylic acid alkyl polymers, methacrylic acid alkyl copolymers, methacrylic acid alkyl ester copolymers, and acrylic acid alkyl / methacrylic acid alkyl copolymers as main components. Here, the main component refers to a component whose content exceeds 50% by mass.

[0072] The (B) polymethacrylic organic particles may include at least one selected from polymethacrylic acid alkyl particles, polymethacrylic acid alkyl ester particles, and acrylic acid alkyl / methacrylic acid alkyl resin particles.

[0073] From the viewpoint of improving swelling properties, the average degree of polymerization of the polymethacrylic acid organic particles (B) may be 1,000 to 50,000, 3,000 to 40,000, or 4,000 to 30,000. When the average degree of polymerization is 1,000 or more, the polymethacrylic acid organic particles (B) swell sufficiently, and the grease composition or the gel composition has pump-out resistance. When the average degree of polymerization is 50,000 or less, the softness of the gel composition becomes good, and the occurrence of cracks or peeling can be reduced.

[0074] The average particle size of the (B) polymethacrylic acid organic particles can be greater than 0.1 μm and less than 10.0 μm, or greater than 0.3 μm and less than 5.0 μm. It should be noted that the average particle size in this specification is the cumulative average particle size D50 based on volume measured by a dynamic light scattering particle size measuring device. When the average particle size of the (B) polymethacrylic acid organic particles is greater than 0.1 μm, the (B) polymethacrylic acid organic particles fill the gaps between the (C) inorganic fillers during swelling, thereby improving thermal conductivity. In addition, when the average particle size of the (B) polymethacrylic acid organic particles is less than 10.0 μm, they are fully dispersed in the present grease composition.

[0075] The polymethacrylic acid-based organic particles (B) may be core-shell type particles. The polymethacrylic acid-based organic particles (B) may be used alone or in combination of two or more.

[0076] (B) Examples of commercially available products of polymethacrylic acid-based organic particles include ZEFIAC F301, F303, F320, F325, F340M, and F351 manufactured by AICA Industries, Ltd.

[0077] The content of (B) polymethacrylic acid organic particles in the present grease composition may be 5 to 30 parts by mass, or 7 to 25 parts by mass, relative to 100 parts by mass of the (A) liquid resin. When the content of (B) polymethacrylic acid organic particles is 5 parts by mass or more, the obtained grease composition can be fully gelled when heated, and pumping due to reduced viscosity can be reduced. In addition, when the content of (B) polymethacrylic acid organic particles is 30 parts by mass or less, the softness of the present gel composition becomes good, and the occurrence of cracks or peeling can be reduced.

[0078] 〔(C) Inorganic filler〕

[0079] The (C) inorganic filler used in the present grease composition is a component that adjusts the viscosity of the present grease composition to a grease-like state together with the (B) polymethacrylic acid-based organic particles. The (C) inorganic filler is not particularly limited as long as it is an inorganic filler used in electronic components, and may be an inorganic filler having thermal conductivity. By using an inorganic filler having thermal conductivity as the (C) inorganic filler, thermal conductivity can be imparted to the present grease composition. Examples of the inorganic filler having thermal conductivity include metal oxides, metal nitrides, nitride compounds, metals, graphite, silicon carbide, silicon compounds, etc. having a thermal conductivity of 10 W / m·K or more. Among them, aluminum oxide, boron nitride, silicon nitride, silicon carbide, and aluminum nitride may be used. In particular, from the viewpoint of high thermal conductivity, aluminum oxide and aluminum nitride may be used. The (C) inorganic filler may be used alone or in combination of two or more.

[0080] The shape of the (C) inorganic filler is not particularly limited, and may be spherical or amorphous. The size of the (C) inorganic filler may be 0.1 to 40 μm or 0.2 to 30 μm in terms of obtaining a uniform grease-like property of the grease composition.

[0081] (C) Inorganic fillers having different average particle sizes can be used in combination, for example, an inorganic filler (Ca) having a large average particle size and an inorganic filler (Cb) having a small average particle size. By combining inorganic fillers having different average particle sizes, the filling rate of the (C) inorganic filler in the present grease composition can be increased. It should be noted that the average particle size of the inorganic fillers (Ca) and (Cb) can be determined in a suitable range according to their materials.

[0082] For example, when the (C) inorganic filler is aluminum nitride particles, aluminum nitride particles (Ca-1) having an average particle size of 20 to 40 μm and aluminum nitride particles (Cb-1) having an average particle size of 1 to 10 μm can be used in combination. By combining aluminum nitride particles (Ca-1) and aluminum nitride particles (Cb-1), the filling rate of the (C) inorganic filler in the present grease composition can be increased.

[0083] When aluminum nitride particles (Ca-1) and aluminum nitride particles (Cb-1) are used in combination, the mass ratio of aluminum nitride particles (Ca-1): aluminum nitride particles (Cb-1) when the total of the mixture is 100 may be in the range of 10:90 to 80:20, or in the range of 50:50 to 80:20. When the mixing ratio is in the range of 10:90 to 80:20, good closest packing can be obtained and the thermal conductivity can be improved.

[0084] In addition, for example, when the inorganic filler (C) is alumina particles, the filling rate of the inorganic filler (C) in the present grease composition can be increased by combining alumina particles (Ca-2) having an average particle size of 7 to 40 μm and alumina particles (Cb-2) having an average particle size of 0.5 to 5 μm. When alumina particles (Ca-2) and alumina particles (Cb-2) are used in combination, the mass ratio of alumina particles (Ca-2):alumina particles (Cb-2) when the total of the mixture is 100 may be in the range of 40:60 to 95:5, or in the range of 50:50 to 90:10. When the mixing ratio is in the range of 40:60 to 95:5, good closest packing can be obtained and the thermal conductivity can be increased.

[0085] The content of (C) inorganic filler in the present grease composition can be 350 to 2000 parts by mass, 500 to 1800 parts by mass, or 800 to 1500 parts by mass relative to 100 parts by mass of (A) liquid resin. When the content of (C) inorganic filler is 350 parts by mass or more, the obtained grease composition can obtain the desired viscosity. In addition, when the content of (C) inorganic filler is 2000 parts by mass or less, the processability during the manufacture of the present grease composition is good, and the grease composition has moderate fluidity. Therefore, the present grease composition can be easily configured on the heat generating component by coating or injection.

[0086] The content of the (C) inorganic filler in the present grease composition may be 70 to 95% by mass, or 80 to 95% by mass, based on the total amount of the present grease composition.

[0087] 〔(D) Silane coupling agent〕

[0088] The present grease composition may contain (D) a silane coupling agent. The (D) silane coupling agent is used to change the surface properties of the (C) inorganic filler, and a known silane coupling agent can be used in this composition.

[0089] As the type of (D) silane coupling agent, any type can be used without particular limitation as long as it contains an amino group, a phenyl group, an epoxy group, an isocyanate group, an isocyanurate group, a vinyl group, a styrene group, a methacrylate group, an acrylic group, a urea group, a titanate group, an acid anhydride group, etc. When the present grease composition contains (D) silane coupling agent, one type thereof may be used alone, or two or more types may be used in combination. When (D) silane coupling agent is used, (A) liquid resin and (B) polymethacrylic organic particles may be mixed after (C) inorganic filler is directly treated, or (A) liquid resin, (B) polymethacrylic organic particles, (C) inorganic filler and (D) silane coupling agent may be mixed together.

[0090] The content of the silane coupling agent (D) in the present grease composition may be 0.02 to 5 parts by mass, or 0.03 to 2 parts by mass, relative to 100 parts by mass of the inorganic filler (C).

[0091] In addition to the above components, the grease composition may also contain antioxidants, weathering stabilizers, heat stabilizers, viscosity modifiers, defoamers, leveling agents, anti-settling agents, dispersants, pigments, antistatic agents, flame retardants and other additives as needed. Each of these additives may be used alone or in combination of two or more.

[0092] The content of each of these additives in the present grease composition may be about 0.05 to 15% by mass, or may be 0.2 to 10% by mass, based on the total amount of the additives, relative to the total amount of the present grease composition.

[0093] In the present grease composition, the total content of (A) the liquid resin, (B) the polymethacrylic acid-based organic particles and (C) the inorganic filler may be 80% by mass or more, 90% by mass or more, or 95% by mass or more.

[0094] The present grease composition can be produced by measuring and blending the above-mentioned (A) liquid resin, (B) polymethacrylic organic particles, (C) inorganic filler, and (D) silane coupling agent and various additives as required so as to achieve the above-mentioned contents, respectively, and mixing and stirring. Such a mixing and stirring method is not particularly limited and can be appropriately selected according to the type, viscosity, and content of each component. Specifically, a method using a mixer such as a dissolver mixer and a homomixer can be cited.

[0095] Furthermore, the mixed and stirred materials may be filtered as necessary, for example, to remove lumps of undispersed components. By performing such filtration, a homogeneous grease composition can be obtained. Furthermore, bubbles generated in the composition during such mixing and stirring can be degassed under reduced pressure. By performing such degassed, the generation of bubbles in the obtained grease composition can be reduced.

[0096] The present grease composition has grease properties. That is, the viscosity of the present grease composition at 25° C. is about 100 to 1000 Pa·s, and may be 110 to 600 Pa·s, or 120 to 500 Pa·s.

[0097] The viscosity can be measured using a rheometer, and specifically, can be measured by the method described in Examples.

[0098] The present grease composition begins to gel at about 60 to 130°C and becomes the present gel-like composition. Therefore, when the present grease composition is used for applications accompanied by temperature changes, if the temperature rises above the gelling start temperature, it is used as the present gel-like composition thereafter. Generally, the fluidity of a resin composition increases as the temperature rises, but the present gel-like composition as a whole has the property of losing fluidity or reducing fluidity to the extent that it only flows slightly. The viscosity of the present gel-like composition at 150°C is about 190 to 10,000 Pa·s, and may also be 200 to 5,000 Pa·s, or 210 to 3,000 Pa·s.

[0099] The viscosity can be measured using a rheometer, and specifically, can be measured by the method described in Examples.

[0100] As an indicator for evaluating the change in properties of the present grease composition, the viscosity ratio (V 150℃ / V 25℃ ). Viscosity ratio (V 150℃ / V 25℃ ) can be measured by rheometer at 25°C. 25℃ ) and the viscosity value at 150℃ (V 150℃ ) and the obtained V 25℃ and V 150℃ When the viscosity ratio (V 150℃ / V 25℃ ) is 1.05 or more, it shows the properties of a gel.

[0101] It should be noted that the viscosity V measured by a rheometer in this specification is a value measured under the prescribed temperature conditions when the temperature is raised to a prescribed temperature using a rheometer (e.g., Kinexuspro+, manufactured by Spectris Corporation). 150℃ It is a value measured at 150°C under the conditions of temperature range: 25 to 200°C, heating rate: 10°C / min, cooling rate: 10°C / min, frequency: 1 Hz (constant), and shear strength: 10 Pa (constant).

[0102] When the viscosity ratio (V 150℃ / V 25℃ ) is 1.05 or more when used in a heat-generating component, the grease composition will gel to become the gel-like composition when the heat-generating component reaches a high temperature. The gel-like composition can be less likely to flow out (pump out) from the heat-generating component.

[0103] The thermal conductivity (W / m·K) in the present grease composition may be 1 W / m·K or more, or 2 W / m·K or more. In addition, after the present grease composition is subjected to a cold and hot cycle under the setting conditions of -40 to 150°C and 1000 cycles, the present grease composition becomes the present gel-like composition, but the thermal conductivity (W / m·K) of the present gel-like composition may be 1 W / m·K or more, or 2 W / m·K or more. It should be noted that there is a tendency that the thermal conductivity (W / m·K) of the gel-like composition obtained by gelling the present grease composition is higher than that of the present grease composition.

[0104] <Electronic components>

[0105] Figure 1 This is a schematic diagram showing a schematic configuration of one embodiment of the electronic component.

[0106] The electronic component 10 of the present embodiment (hereinafter, also referred to as "the present electronic component") is as follows: Figure 1 As shown, there are a heating element 1, a heat sink 2, and the present grease composition 3 disposed between the heating element 1 and the heat sink 2. The heating element 1 can be disposed on a substrate 4. In addition, the substrate 4 on which the heating element 1 is disposed and the heat sink 2 can be fixed by screws 5.

[0107] As the electronic component, for example, electronic equipment, inverters, etc. can be cited, and electronic equipment can be cited. In the case where the electronic component is an electronic device, as the heating element, IC chips, CPU chips, GPU chips, etc. can be cited. In the case where the electronic component is an inverter, as the heating element, IGBT, etc. can be cited, and as the heat sink, etc. can be cited.

[0108] As a method for arranging the present grease composition between the heating element and the heat sink, the above-mentioned coating or injection can be cited. Coating or injection can be performed by a method similar to that of general coating or injection of grease products. In the present electronic component, when the present grease composition is coated or injected between the heating element and the heat sink, when the heating element reaches a high temperature, for example, about 150°C, during the process, the present grease composition gels to become the present gel-like composition, and in subsequent use, it exists between the heating element and the heat sink in the state of the present gel-like composition.

[0109] From the viewpoint of improving pump-out resistance and heat dissipation, the thickness of the grease composition or the gel composition disposed between the heat generating element and the heat dissipating element may be 5 to 500 μm, or 50 to 400 μm.

[0110] Example

[0111] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0112] [Each ingredient]

[0113] The materials used in the preparation of the compositions of Examples and Comparative Examples are as follows.

[0114] (A) Liquid resin

[0115] A-1: Alkyl diphenyl ether (manufactured by MORESCO Co., Ltd., LB-100, viscosity at 25°C: 200 mPa·s, oxidation: <0.1 mgKOH / g, mass reduction rate: <0.1%, SP value: 7.3 to 9.1).

[0116] A-2: Pentaphenyl ether (MORESCO Co., Ltd., S-3105, viscosity at 25°C: 570 mPa·s, oxidation: <0.1 mgKOH / g, mass reduction rate: <0.1%, SP value: 7.3 to 9.1).

[0117] A-3: Tetraphenyl ether (manufactured by MORESCO Co., Ltd., S-3103, viscosity at 25°C: 240 mPa·s, oxidation: <0.1 mgKOH / g, mass reduction rate: <0.1%, SP value: 7.3 to 9.1).

[0118] A-4: monoalkyl tetraphenyl ether (manufactured by MORESCO Co., Ltd., S-3101, viscosity at 25°C: 470 mPa·s, oxidation: <0.1 mgKOH / g, mass reduction rate: <0.1%, SP value: 7.3 to 9.1).

[0119] A-5: dialkyl tetraphenyl ether (manufactured by MORESCO Co., Ltd., S-3230, viscosity at 25°C: 800 mPa·s, oxidation: <0.1 mgKOH / g, mass reduction rate: <0.1%, SP value: 7.3 to 9.1).

[0120] A-6: polyester polyol (manufactured by NOF Corporation, UNISTER (registered trademark) HR-32, viscosity at 25°C: 480 mPa·s, oxidation: 0.1 mgKOH / g, mass reduction rate: <0.1%, SP value: 7.3 to 9.1).

[0121] A-7: polyester polyol (UNISTER (registered trademark) H-609BR manufactured by NOF Corporation, viscosity at 25°C: 900 mPa·s, oxidation: 0.1 mgKOH / g, mass reduction rate: <0.1%, SP value: 7.3 to 9.9).

[0122] A-8: Polytetrahydrofuran-diparaaminobenzoate (manufactured by Kumiai Chemical Industry Co., Ltd., ELASMER 1000P, viscosity at 25°C: 8000 mPa·s, amine value: 84.4 mgKOH / g, mass reduction rate: <0.1%, SP value: 8.9 to 11.5).

[0123] (A) The viscosity of the liquid resin at 25° C. was measured using an E-type viscometer (VISCOMETER TPE-100 manufactured by TOKISANGYO).

[0124] The mass reduction rate of the (A) liquid resin was calculated as the mass change rate (reduction rate) before and after heating 30 g of the (A) liquid resin in an oven at 150° C. for 24 hours.

[0125] (B) Polymethacrylic acid organic particles

[0126] B-1: methacrylic acid alkyl polymer (ZEFIAC F320 manufactured by AICA INDUSTRY CO., LTD., average particle size: 2 μm, average degree of polymerization: 30,000).

[0127] B-2: methacrylic acid alkyl copolymer (ZEFIAC F340M manufactured by AICA INDUSTRY CO., LTD., average particle size: 1 μm, average degree of polymerization: 30,000).

[0128] B-3: methacrylic acid alkyl polymer (ZEFIAC F325 manufactured by AICA INDUSTRY CO., LTD., average particle size: 1 μm, average degree of polymerization: 40,000).

[0129] B-4: an alkyl methacrylate copolymer (ZEFIAC F303 manufactured by AICA Industries, Ltd., average particle size: 2 μm, average degree of polymerization: 20,000).

[0130] B-5: an alkyl methacrylate copolymer (ZEFIAC F301 manufactured by AICA INDUSTRY CO., LTD., average particle size: 2 μm, average degree of polymerization: 20,000).

[0131] B-6: an alkyl acrylic acid / alkyl methacrylic acid copolymer (manufactured by AICA INDUSTRY CO., LTD., ZEFIAC F351, average particle size: 0.5 μm, average degree of polymerization: 40,000).

[0132] Particles other than (B) polymethacrylic acid organic particles

[0133] Resin particles 1: a cross-linked product of methyl methacrylate (manufactured by Nippon Shokubai Co., Ltd., epostar (registered trademark) MA1002, average particle size: 2 μm).

[0134] Resin particles 2: a cross-linked product of methyl methacrylate (manufactured by Nippon Shokubai Co., Ltd., epostar (registered trademark) MA1004, average particle size: 4 μm).

[0135] Resin particles 3: silicone rubber (manufactured by Shin-Etsu Chemical Co., Ltd., KMP-597, average particle size: 1 μm, average degree of polymerization: 30,000).

[0136] Resin particles 4: fluorine-based particles (manufactured by AGC Corporation, L-173JE, average particle size: 2 μm, average degree of polymerization: 30,000).

[0137] Methacrylate copolymer (liquid) (manufactured by Toagosei Co., Ltd., UH-2190, average degree of polymerization: <1000).

[0138] (C) Inorganic fillers

[0139] Ca-1: aluminum nitride particles (manufactured by Furukawa Electric Co., Ltd., FAN-f30, average particle size: 30 μm).

[0140] Cb-1: aluminum nitride particles (manufactured by Furukawa Electric Co., Ltd., FAN-f05, average particle size: 5 μm).

[0141] Ca-2: Alumina particles (manufactured by Sumitomo Chemical Co., Ltd., AA-18, average particle size: 20 μm).

[0142] Cb-2: Alumina particles (manufactured by Sumitomo Chemical Co., Ltd., AA-1.5, average particle size: 1.5 μm).

[0143] (D) Silane coupling agent

[0144] · D-1: 3-glycidyloxypropyltrimethoxysilane (Dynasylan (registered trademark) GLYMO, manufactured by Evonik Japan Ltd.).

[0145] The solubility of (A) liquid resin, (B) polymethacrylic acid organic particles, and resin particles 1 to 4 other than (B) polymethacrylic acid organic particles was studied. Ten solvents shown in Table 1 were prepared, and 0.1 g of component (A), component (B), and resin particles 1 to 4 were added to 5 g of these solvents with different SP values, respectively, and stirred for 1 hour at room temperature (25°C) using a stirrer. After stirring, the solubility of these was confirmed.

[0146] Regarding solubility, the case where the mixture becomes transparent after stirring is considered to be fully dissolved and is evaluated as "A", and the case where the mixture becomes translucent or turbid is considered to be incompletely dissolved and is evaluated as "C". The evaluation results are shown in

[0147] Table 1.

[0148]

[0149] [Examples 1 to 23, Comparative Examples 1 to 5]

[0150] The above materials were prepared according to the compositions shown in Table 2-1 to Table 2-3 to obtain grease compositions of Examples 1 to 23 and Comparative Examples 1 to 5. It should be noted that blank columns in Table 2-1 to Table 2-3 indicate that no compounding was performed. In addition, the following evaluations were performed using the grease compositions obtained in each example. The results are shown in Table 2-1 to Table 2-3.

[0151] (1) Determine viscosity using a rheometer

[0152] Using a rheometer (Kinexus pro+, manufactured by Spectris Corporation), 5 to 10 g of the grease composition was measured under the conditions of temperature range: 25 to 200°C, heating rate: 10°C / min, frequency: 1 Hz (constant), and shear strength: 10 Pa (constant). The viscosity at 25°C is denoted as V 25℃ , the viscosity at 150°C is recorded as V 150℃ In addition, by V 25℃ and V 150℃ The viscosity ratio (V 150℃ / V 25℃ ).

[0153] (2) Pumping resistance

[0154] 0.5 to 1.0 g of the grease composition was dropped onto the approximate center of a glass slide provided with a 150 μm spacer, and the grease composition was sandwiched between glass slides without spacers (short side 26 mm × long side 76 mm × thickness 1.3 mm) so that the grease composition became a circle with a diameter of 10 mm. At this time, the grease composition did not extend beyond the glass slide. The two sides of the three-layer body of glass slide / grease composition / glass slide were clamped with a clamp. The clamp applied a clamping force of 2.5 kg. The three-layer body was placed vertically with the long side facing downward, and a hot and cold cycle test was performed using a hot and cold cycle tester (trade name: TSA-100S-W, manufactured by ESPEC Co., Ltd.) under the setting conditions of -40 to 150°C and 1000 cycles (holding time: 30 minutes, heating time: 10°C / second, cooling time: 10°C / second). After the thermal cycle test, the three-layer body was taken out, and the state of the grease composition or its gelled product between the slide glasses was visually observed and evaluated according to the following criteria.

[0155] A: The droplet is less than 3mm.

[0156] C: The droplet is 3 mm or larger.

[0157] (3) Generation of voids

[0158] 0.5-1.0 g of the grease composition was dropped onto the approximate center of a glass slide with a 150 μm spacer, and the grease composition was clamped with a glass slide without a spacer (short side 26 mm × long side 76 mm × thickness 1.3 mm) so that the grease composition became a circle with a diameter of 10 mm. At this time, the grease composition did not extend beyond the glass slide. The two sides of the three-layer body of glass slide / grease composition / glass slide were clamped with a clamp. The clamp applied a clamping force of 2.5 kg.

[0159] Place the sample clamped with a clamp flat on a hot plate adjusted to 150°C and heat for 1 minute. Use a microscope (nano.Capture PRO, manufactured by Sightron) to collect images of the state after heating for 1 minute, and use image processing software Image-J to implement binarization processing. Apply the binarized image, calculate the porosity by the following formula, and evaluate according to the following criteria. It should be noted that in the following evaluation, A and B are considered qualified.

[0160] Porosity (%) = Area of ​​voids (mm 2 ) / Area of ​​grease diameter 10mm (mm 2 )

[0161] A: The void ratio is less than 3%.

[0162] B: The porosity is 3% or more and less than 6%.

[0163] C: The void ratio is 6% or more.

[0164] (4) Thermal conductivity (before and after hot and cold cycle test, after continuous heating at 150°C)

[0165] The thermal conductivity was measured using a diffusion coefficient measuring device (LFA467, manufactured by NETZSCH Japan Co., Ltd.). The grease composition was added to an aluminum cup container with a diameter of 12.7 mm and covered with an aluminum lid with a diameter of 9 mm to form a three-layer structure. The grease composition was adjusted so that the thickness of the grease composition was 350 μm ± 50 μm, and was set on a liquid measurement stand. The thermal diffusivity obtained by the xenon flash method was calibrated to remove the thermal diffusivity of aluminum to obtain the thermal diffusivity including the interface thermal resistance. The obtained thermal diffusivity including the interface thermal resistance, the density of the grease composition, and the specific heat were inserted into the following formula (1) to calculate the thermal conductivity, which was recorded as the thermal conductivity before the hot and cold cycle test. The density was measured using a high-precision electronic densitometer (SD-200L, manufactured by ALFA MIRAGE Co., Ltd.). The specific heat was measured using a differential scanning calorimeter (DSC-6200, manufactured by Seiko Instruments Co., Ltd.).

[0166] Thermal conductivity (W / m·K) = thermal diffusivity (mm 2 / s)×density(g / cm 3 )×specific heat (J / (kg·K))···(1)

[0167] In the above-mentioned evaluation of pump-out resistance, the grease composition or its gelled product between the glass slides is taken out from the three-layer body after the hot and cold cycle test, and the thermal conductivity is calculated using the same method as above (4), and recorded as the thermal conductivity after the hot and cold cycle test.

[0168] 50 g of the grease composition was placed in a 50 cc glass tube and heated in a 150°C heating drying furnace for 1000 hours to obtain a gel. After the obtained gel was cooled to room temperature (25°C), the thermal conductivity was calculated using the same method as in (4) above and recorded as the thermal conductivity after continuous heating at 150°C.

[0169] (5) Mass reduction rate (%)

[0170] 50 g of the grease composition was placed in a 50 cc glass tube and subjected to a thermal cycle test using a thermal cycle tester at -40 to 150°C for 1000 cycles. The mass reduction rate (rate of change) was calculated from the mass W1 of the grease composition before the thermal cycle test and the mass W2 after the thermal cycle test.

[0171] (6) Thermal resistance

[0172] A grease composition with a thickness of 150 μm was applied to the metal base substrate side of a semiconductor power module component made by Infineon (106 mm long × 61 mm wide × 30 mm thick, TjMAX of the component: 150°C), and set on a copper plate with a length of 210 mm × a width of 60 mm × a thickness of 10 mm. The setting is to set screws in six screw holes and fix them with a tightening torque of 200 cN / cm. The copper plate with the semiconductor power module set is placed vertically, and the components inside the component are heated by applying voltage to the terminals of the semiconductor power module. The voltage is turned on / off for 5000 cycles (holding time: 3 seconds), and the thermal resistance after 5000 cycles is evaluated.

[0173]

[0174]

[0175]

[0176]

[0177] Table 2-3

[0178]

[0179] From the results shown in Tables 2-1 to 2-3, it can be seen that since the viscosity of the grease composition of the present invention is 110 to 590 Pa·s at 25°C, it has good processability, good fluidity and is easy to apply to heat-generating components. In addition, since the wettability and followability of the interface are good, low thermal resistance can be achieved. In addition, the grease composition gels into the present gel-like composition due to the heat generated by the heat-generating component, which makes it difficult to pump out. After the hot and cold cycle test, the thermal conductivity is increased by more than 0.5 W / m·K.

[0180] Industrial Applicability

[0181] As described above, the present grease composition is easy to apply to heat-generating components, and after application, even if the heat-generating components reach a high temperature, such as about 150°C, it will gel and inhibit the viscosity from decreasing, making it difficult to pump out. On this basis, since the thermal conductivity of the present grease composition is increased by more than 0.5 W / m·K, it can compensate for the decrease in heat dissipation accompanying the degradation of components during long-term use, and can exhibit stable performance.

[0182] Therefore, the present grease composition is useful as a grease for transferring heat generated from heat-generating components of electronic devices, such as IC chips, CPU chips, GPU chips, IGBTs, etc., which generate local heat, to heat dissipation sites such as heat sinks.

[0183] Description of Reference Numerals

[0184] 1 Heating element

[0185] 2 Heat sink

[0186] 3 Grease composition

[0187] 4 substrate

[0188] 5 Screws

[0189] 10 Electronic components.

Claims

1. A grease composition, characterized in that: Contains (A) a liquid resin, (B) polymethacrylic acid organic particles and (C) an inorganic filler, The (A) liquid resin comprises at least one selected from polyester polyol, polyether containing phenyl ether and polytetrahydrofuran-dipara-aminobenzoate, The (B) polymethacrylic acid organic particles are dissolved in an organic solvent having a solubility parameter, i.e., SP value, of 7.8 to 10.1, The (C) inorganic filler contains aluminum oxide particles or aluminum nitride particles.

2. The grease composition according to claim 1, wherein The (B) polymethacrylic acid organic particles have an average particle size of 0.1 to 10.0 μm.

3. The grease composition according to claim 1, wherein The (B) polymethacrylic acid-based organic particles have an average degree of polymerization of 1,000 to 50,000.

4. The grease composition according to claim 2, wherein The (B) polymethacrylic acid-based organic particles have an average degree of polymerization of 1,000 to 50,000.

5. The grease composition according to claim 1, wherein The (B) polymethacrylic organic particles include at least one selected from polymethacrylate alkyl ester particles and acrylic acid alkyl / methacrylic acid alkyl resin particles.

6. The grease composition according to claim 2, wherein: The (B) polymethacrylic organic particles include at least one selected from polymethacrylate alkyl ester particles and acrylic acid alkyl / methacrylic acid alkyl resin particles.

7. The grease composition according to claim 3, wherein The (B) polymethacrylic organic particles include at least one selected from polymethacrylate alkyl ester particles and acrylic acid alkyl / methacrylic acid alkyl resin particles.

8. The grease composition according to claim 4, wherein The (B) polymethacrylic organic particles include at least one selected from polymethacrylate alkyl ester particles and acrylic acid alkyl / methacrylic acid alkyl resin particles.

9. The grease composition according to any one of claims 1 to 8, wherein The (A) liquid resin contains polyether, and the proportion of the polyether in the (A) liquid resin is 50 to 95% by mass.

10. The grease composition according to any one of claims 1 to 8, wherein The grease composition is gelled by heating.

11. The grease composition according to claim 9, wherein The grease composition is gelled by heating.

12. An electronic component, wherein: With: heating element; a heat sink; and The grease composition according to any one of claims 1 to 11 disposed between the heat generating element and the heat radiating element.

Citation Information

Patent Citations

  • Thermal conductive silicone putty composition

    JP2017002179A

  • Thermal conductive oil composition, heat release agent and electronic device

    JP2019089924A

  • Viscosity index improver, lubricant oil additive, and lubricant oil composition

    CN103443258A

  • Rubber composition and pneumatic tire using same

    CN105377974A